MENIMBUN BARANG (IHTIKAR) PERSPEKTIF HADIS (SUATU KAJIAN TEMATIK) - Andi Intan Cahyani (El-Iqthisadi, 2020)
AbstractHadith research on ihtikar and especially on the hadith relating to the forbidden ihtikar which is the object of research in this paper is the quality of authentic Hadith, both viewed from the sanad and its mature quality. Therefore, this hadith can be used as a legal basis in establishing Islamic law. The Hadith states the prohibition on doing ihtikar with the phrase "la yahtakiru illa khathi’un", regarding the hadith jumhur Ulama agreed on the prohibition of ihtikar. However, they differed on the method used to determine the prohibition of ihtikar. Because ihtikar's actions can cause instability in society, ihtikar's perpetrators are very appropriate if given severe criminal sanctions and in accordance with their actions.Keywords: Ihtikar, Haram, Law, Jumhur Ulama.AbstrakPenelitian hadis tentang ihtikar dan terkhusus lagi pada hadis yang berkaitan dengan keharaman ihtikar yang menjadi obyek penelitian dalam makalah ini adalah kualitas Hadis shahih, baik dilihat dari sanad maupun kualitas matangnya. Oleh karena itu, hadis tersebut dapat dijadikan landasan hukum dalam penetapan hukum Islam. Hadis menyatakan larangan melakukan perbuatan ihtikar dengan ungkapan “la yahtakiru illa khathi’un”, mengenai hadis tersebut jumhur Ulama sepakat mengenai keharaman ihtikar. Namun demikian, mereka berbeda pendapat mengenai cara yang digunakan dalam menetapkan keharaman ihtikar.  Oleh karena tindakan ihtikar dapat menimbulkan instabilitas dalam masyarakat, maka pelaku ihtikar sangat tepat bila diberi sanksi pidana yang berat dan sesuai dengan perbuatannya.Kata Kunci: Ihtikar, Haram, Hukum, Jumhur Ulama.